Importance of Interdisciplinary Courses in Engineering Education - Manju, M. B.; Nikhil, K. S.; Nishanth, D.; Sai Vignesh, K. S.; Anupama, B. S.; Murthy, Madhav (Journal of Engineering Education Transformations, 2025)
Interdisciplinary courses are essential in aligning the students towards the current trend. It helps in reducing the gap between colleges and industries. It helps in crossing boundaries and creating something new. This work is a study into the necessity of Interdisciplinary Courses in the present engineering education. Efforts were put up to gather information from students pursuing their engineering degree all over India. Survey was conducted through questionnaires. The study was based on 3 criteria: awareness, necessity and evaluation of Interdisciplinary Courses. Majority of the surveytakers converged on the need of Interdisciplinary courses in the present engineering scenario.